Development of Islamic Religious Education Modules to Improve Understanding of Islam among Teenagers - Pein, Maulana (PT. Anagata Sembagi Education, 2025)
The understanding of Islam among adolescents can be improved through the development of interactive and relevant Islamic religious education modules. This study aims to identify the characteristics of an effective module, analyze the factors that influence adolescents' understanding, and make recommendations based on previous research. The method used is Systematic Literature Review (SLR) by collecting and analyzing various related studies. The results showed that technology-based and interactive modules, such as the use of videos, animations, and quizzes, can increase adolescents' interest and understanding of Islamic teachings. The success of this module also depends on the support of teachers, parents, and the community. Therefore, module development must continue to be adapted to the times so that it is effective in building understanding and Islamic morals among adolescents.